Experimental Phytochemical Techniques - Raaman N.; Raaman N. (New Delhi New India publishing, 2011)
experimental data using the phytochemical techniques and medicinal plants
ayurveda clinical studies artemisia pallens
Keywords: ayurveda,clinical studies